2019
DOI: 10.1080/15476286.2019.1700058
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation by Foot-and-mouth disease virus infection mainly induced by viral RNA and non-structural protein 2B

Abstract: Foot-and-mouth disease virus (FMDV) is a positive-strand RNA virus of the family Picornaviridae. Early studies show that some viruses of Picornaviridae, such as EMCV and EV71, induce NLRP3 inflammasome activation. Our current study demonstrates that FMDV induces the secretion of caspase-1 and interleukin 1 beta (IL-1β), as well as activates the NLRP3 inflammasome in a doseand time-dependent manner. Meanwhile, NLRP3 inflammasome can suppress FMDV replication during virus infection. Both FMDV RNA and viroporin 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 68 publications
2
31
1
Order By: Relevance
“…Another member of the picornaviridae family is foot-and-mouth disease virus (FMDV). Both FMDV RNA and viroporin 2B were shown to stimulate NLRP3 inflammasome activation by elevation of intracellular ion, but not dependent on mitochondrial reactive oxygen species (ROS) and lysosomal cathepsin B [107].…”
Section: Encephalomyocarditis Virus: 2b Viroporinmentioning
confidence: 99%
“…Another member of the picornaviridae family is foot-and-mouth disease virus (FMDV). Both FMDV RNA and viroporin 2B were shown to stimulate NLRP3 inflammasome activation by elevation of intracellular ion, but not dependent on mitochondrial reactive oxygen species (ROS) and lysosomal cathepsin B [107].…”
Section: Encephalomyocarditis Virus: 2b Viroporinmentioning
confidence: 99%
“…RIG-I-mediated activation of NF-κB requires MAVS and a complex of CARD9 and Bcl-10 adaptor proteins [ 88 ]. RIG-I also binds to the adaptor protein ASC and stimulates caspase-1-dependent inflammasome activation by a mechanism independent of MAVS, which suggests that RIG-I activates the inflammasome in response to certain RNA viruses [ 88 , 89 , 90 ].…”
Section: Mitochondrial Antiviral Signaling (Mavs)mentioning
confidence: 99%
“…The FMDV 2B protein activates NLRP3 inflammasomes by decreasing [K + ] cyt and increasing [Ca 2+ ] cyt , causing the release of IL-1β. 152 This evidence shows that the FMDV 2B protein can activate NLRP3 inflammasomes via ion channel formation in a ROS-independent manner.…”
Section: Rna Viruses That Activate Nlrp3 Inflammasomesmentioning
confidence: 81%
“… 151 The 2B protein of FMDV, a non-structural protein, can induce NLRP3 activation and IL-1β secretion. 152 It has been reported that signal 2 for NLRP3 activation in response to FMDV infection involves K + efflux and Ca 2+ influx but is ROS and cathepsin B independent. The 2B protein can change the membrane permeability, causing an imbalance regarding [Ca 2+ ] cyt in the host cell.…”
Section: Rna Viruses That Activate Nlrp3 Inflammasomesmentioning
confidence: 99%